Viola odorata Alleviates Airway Inflammation and Histopathological Changes in an Animal Model of Allergic Asthma - Moones Fallah; Arman Musapour; Homa Hajimehdipoor; Fatemeh Jafari; Sadegh Rajabi* (Iranian Society of Pharmacognosy, 2024)
Background and objectives: Asthma is a chronic airway inflammatory disease. Viola odorata has been traditionally used to treat inflammatory diseases. This study was conducted to explore the anti-inflammatory effects of V. odorata aqueous extract on a murine model of asthma. Methods: Forty-eight Balb/c female mice were divided into six groups of eight animals. The healthy controls received distilled water and other groups became asthmatic using ovalbumin. Then, one group received dexamethasone, and the extract (100, 200, and 400 mg/kg) was administered to three groups for a week. Subsequently, the number of eosinophils, and the levels of interleukins 4, 5, and 13 were measured in bronchoalveolar lavage fluid (BALF) samples. Histopathological changes were analyzed in lung tissues. Results: Eosinophils count and the levels of interleukins 4, 5, and 13 in BALF specimens significantly reduced. Hyperplasia of goblet cells, lymphoid tissue hyperplasia, and peribronchial and perivascular inflammations decreased in the extract-treated mice. The effects of V. odorata aqueous extract on all parameters were comparable with dexamethasone. Conclusion: The present study is the first report of anti-inflammatory activities of V. odorata aqueous extract in a mouse model of allergic asthma. Therefore, these data may suggest V. odorata as a promising drug to treat asthma-induced inflammation.